2007
DOI: 10.1016/j.ces.2006.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Batch production of micron size particles from poly(ethylene glycol) using supercritical CO2 as a processing solvent

Abstract: The major advantage of using supercritical carbon dioxide (CO 2 ) as a solvent in polymer processing is an enhancement in the free volume of a polymer due to dissolved CO 2 , which causes a considerable reduction in the viscosity. This allows spraying the polymer melt at low temperatures to produce micron size particles. We have used supercritical CO 2 as a solvent for the generation of particles from poly(ethylene glycol) (PEG) of different molecular weights. Since PEG is a hydrophilic compound, it is a most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 11 publications
(14 reference statements)
2
24
0
Order By: Relevance
“…It might be explained that CO 2 could not escape easily due to rapid solidification of the particles due to the temperature effect on particle formation. Nalawade et al [1] also reported the similar effect of temperature on micro particle formation by PGSS using SC-CO 2 . In contrast, at constant temperature the particle size of functional compounds with PEG decreased with the increase in pressure.…”
Section: -1 Analysis Of Sem Imagesmentioning
confidence: 71%
See 2 more Smart Citations
“…It might be explained that CO 2 could not escape easily due to rapid solidification of the particles due to the temperature effect on particle formation. Nalawade et al [1] also reported the similar effect of temperature on micro particle formation by PGSS using SC-CO 2 . In contrast, at constant temperature the particle size of functional compounds with PEG decreased with the increase in pressure.…”
Section: -1 Analysis Of Sem Imagesmentioning
confidence: 71%
“…Pharmaceutical industries always need fine particles without using organic solvents [1]. Traditionally, some methods are used for producing fine particles, including milling, grinding, spray drying, and recrystallization from solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 has been exploited as a solvent for polymerisations [7,8], as a foaming agent [1,[9][10][11][12][13], for precipitation/separation [14], particle formation [15,16] and encapsulation [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years interest in the use of compressed CO2 as a reaction medium or plasticiser for polymer synthesis and processing has increased steeply (32)(33)(34)(35). CO2 has been exploited as a solvent for polymerisations (36,37), as a foaming agent (32,38), for precipitation/separation (39), particle formation (40,41) and encapsulation (42). High-pressure CO2 is a good solvent for many small molecules and it is very effective at plasticising and effectively liquefying many polymers at temperatures below their glass transition temperature (Tg) and melting point (Tm) (33,41,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52), therefore opening up new opportunities for polymer synthesis and modification.…”
Section: Introductionmentioning
confidence: 99%